2018
DOI: 10.3390/cryst8010039
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture and Crystallization of Ammonia Bicarbonate in a Lab-Scale Scrubber

Abstract: A lab-scale bubble-column scrubber is used to capture CO 2 gas and produce ammonia bicarbonate (ABC) using aqueous ammonia as an absorbent under a constant pH and temperature. The CO 2 concentration is adjusted by mixing N 2 and CO 2 in the range of 15-60 vol % at 55 • C. The process variables are the pH of the solution, temperature, gas-flow rate and the concentration of gas. The effects of the process variables on the removal efficiency (E), absorption rate (R A ) and overall mass-transfer coefficient (K G a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In addition, the parameter importance analysis shows γ > pH > T, indicating that the liquid gas contact is significant for CO 2 loading. For the sake of caparison, two solvents, MEA [35] and aqueous ammonia [36], were used in the bubble-column scrubbers for CO 2 capture, and they are also exhibited Figure 7. It was found that most of the data falls in between the error range.…”
Section: Loading Of Co 2 At the Final Stagementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the parameter importance analysis shows γ > pH > T, indicating that the liquid gas contact is significant for CO 2 loading. For the sake of caparison, two solvents, MEA [35] and aqueous ammonia [36], were used in the bubble-column scrubbers for CO 2 capture, and they are also exhibited Figure 7. It was found that most of the data falls in between the error range.…”
Section: Loading Of Co 2 At the Final Stagementioning
confidence: 99%
“…This could be done by increasing the pH of the solution. In addition, the K G a values obtained in the two solvents, MEA [35] and aqueous ammonia [36], which were used in the bubble-column scrubbers for CO 2 absorption, were shown in the same figure for comparison. It was found that the reported data for the two solvents were close to that obtained in this work.…”
Section: Overall Mass-transfer Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…MEA exhibits excellent absorption efficiency, therefore, it has been adopted in several studies. In the previous studies, to understand the relationship between absorption and crystallization in this system, the quasi-steady operation and shell balance were adopted to obtain the equation of absorption rate, and a two-film model was used to describe the mass transfer of CO 2 in the absorption solvent to determine the overall mass transfer coefficient [16,23]. Hence, the results of this study were compared with those of the previous studies in terms of the above-mentioned theory to understand the commercial value of this process.…”
Section: Introductionmentioning
confidence: 99%
“…In the second paper, Chen [7] proposed a CO 2 capture system the efficiency of which was experimentally determined. The carbon dioxide was converted into ammonia bicarbonate using aqueous ammonia.…”
mentioning
confidence: 99%